THE URGENCY OF IMPLEMENTING PAIKEM METHOD TO INCREASE STUDENT MOTIVATION IN ISLAMIC RELIGIOUS EDUCATION LESSONS - Pradana, Yudik; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In essence, learning is a transactional communication process between teachers and students where the process is mutually beneficial. Learning is the procedures and methods adopted by teachers to make it easier for students to actively learn in order to achieve learning objectives. However, the process does not run easily, the method that must be taken if there are problems in the learning process. And of course in schools there are many problems in PAI subjects. In addition, a teacher is also required to have good ability to determine conditions. Therefore, it is important here to be able to apply one of the learning methods, namely PAIKEM, it is hoped that this method can increase students' attention in participating in learning and can also stimulate students' learning motivation. This research uses descriptive qualitative research where data collection is carried out using observation, interview and documentation techniques. The aim of this research is to determine the implementation of the PAIKEM method in PAI subjects at MA Mambaul Ulum District. Bangkalan. The research results show that the implementation of the PAIKEM method in increasing student learning motivation at MA Mambaul Ulum District. Bangkalan is still not optimal because there are still many subject teachers, especially PAI subject teachers, who are not optimal in implementing the PAIKEM method in the classroom.